2012
DOI: 10.1016/j.jse.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glenoid inclination on routine clinical radiographs and computed tomography examinations of the shoulder

Abstract: BACKGROUND: Accurate assessment of glenoid inclination is of interest for a variety of conditions and procedures. The purpose of this study was to develop an accurate and reproducible measurement for glenoid inclination on standardized anterior-posterior (AP) radiographs and on computed tomography (CT) images. MATERIALS AND METHODS: Three consistently identifiable angles were defined: Angle by line AB connecting the superior and inferior glenoid tubercle (glenoid fossa) and the line identifying the scapular sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(118 citation statements)
references
References 20 publications
5
110
0
3
Order By: Relevance
“…1 The inclination angle was calculated here only to make comparisons with other similar studies and our measured inclination was consistent with reported values for normal scapulae. 18,20,25,30 In our OA scapulae, the inclination decreased, especially in group C. Instead of using the version V and orientation O proposed here, the 3D orientation of the glenoid could be characterised by the inclination and another angle measured in the plane perpendicular to the scapula. The radius of the fitted sphere was in the same range as the reported values, 21,22,35,36 as was the RMSE.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…1 The inclination angle was calculated here only to make comparisons with other similar studies and our measured inclination was consistent with reported values for normal scapulae. 18,20,25,30 In our OA scapulae, the inclination decreased, especially in group C. Instead of using the version V and orientation O proposed here, the 3D orientation of the glenoid could be characterised by the inclination and another angle measured in the plane perpendicular to the scapula. The radius of the fitted sphere was in the same range as the reported values, 21,22,35,36 as was the RMSE.…”
Section: Discussionmentioning
confidence: 88%
“…Our scapular axis does not pass through the glenoid centre, but follows the supraspinatus groove, as already proposed. 30 It is nearly parallel to the usual transverse scapular axis passing from the medial point of the scapula and the glenoid centre.…”
Section: Discussionmentioning
confidence: 97%
“…Technique: ratio of the glenoid-acromion distance to the glenohumeral distance. Specifically, the distance between the glenoid axis and the most lateral aspect of the acromion divided by the distance between the glenoid axis and the most lateral aspect of the humerus [2,25] Glenoid inclination (radiographic) View: anterior-posterior Technique: intersection between the glenoid axis and a line drawn along the floor of the supraspinatus fossa [22] Minimum subacromial space width (radiographic and ultrasonic)…”
Section: Morphological Measurement Proceduresmentioning
confidence: 99%
“…Lastly, while all injury classification ranges were based on available data, the glenoid inclination classification may slightly diverge from those in the literature due to the variation in measurement technique. The measurement method in this research was one established recently by Maurer et al [22] that was shown to reliably measure inclination on radiographs. Thus, the injury classification of approximately 90°b y Hughes et al [17] was modified to 95°to include the difference in measurement technique.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation